mRNA Translation Is Dynamically Regulated to Instruct Stem Cell Fate - Wang, Ruoxu; Amoyel, Marc (Frontiers in Molecular Biosciences, 2022)
Stem cells preserve tissue homeostasis by replacing cells lost through damage or natural turnover. Thus, stem cells and their daughters can adopt two identities, characterised by different programmes of gene expression and metabolic activity. The composition and regulation of these programmes has been extensively studied, particularly by identifying transcription factor networks that define cellular identity and the epigenetic changes that underlie the progressive restriction in gene expression potential. However, there is increasing evidence that post-transcriptional mechanisms influence gene expression in stem cells and their progeny, in particular through the control of mRNA translation. Here, we review the described roles of translational regulation in controlling all aspects of stem cell biology, from the decision to enter or exit quiescence, to maintaining self-renewal and promoting differentiation. We focus on mechanisms controlling global translation rates in cells, mTOR signalling, eIF2ɑ phosphorylation and ribosome biogenesis, and how they allow stem cells to rapidly change their gene expression in response to tissue need or environmental changes. These studies emphasise that translation acts as an additional layer of control in regulating gene expression in stem cells, and that understanding this regulation is critical to gaining a full understanding of the mechanisms that underlie fate decisions in stem cells.